2013
DOI: 10.1093/jjfinec/nbt003
|View full text |Cite
|
Sign up to set email alerts
|

The Price Impact of Order Book Events

Abstract: We study the price impact of order book events -limit orders, market orders and cancelations -using the NYSE TAQ data for 50 U.S. stocks. We show that, over short time intervals, price changes are mainly driven by the order flow imbalance, defined as the imbalance between supply and demand at the best bid and ask prices. Our study reveals a linear relation between order flow imbalance and price changes, with a slope inversely proportional to the market depth. These results are shown to be robust to seasonality… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
322
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(409 citation statements)
references
References 53 publications
24
322
4
Order By: Relevance
“…At the beginning of the continuous trading day, volume price impact is significantly higher. This is consistent with Cont et al (2011) who show that there is lower depth in the morning because of information asymmetry.…”
Section: Figure 3: Adjusted Amihud Ratio Seasonalitysupporting
confidence: 92%
See 2 more Smart Citations
“…At the beginning of the continuous trading day, volume price impact is significantly higher. This is consistent with Cont et al (2011) who show that there is lower depth in the morning because of information asymmetry.…”
Section: Figure 3: Adjusted Amihud Ratio Seasonalitysupporting
confidence: 92%
“…Consistent with Cont et al (2011), we show that trade-based and order bookbased liquidity measures are informative of forthcoming price impact. We also find support for Jain et al (2011) who show that the order book bid side is more informative than the ask side.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…For instance, the price impact of a market order is generally believed to be larger than that of a limit order, and the empirical study by Cont et al [19] suggests that the price impact is more or less linear at the trade level.…”
Section: Optimal Placementmentioning
confidence: 99%
“…Order flow imbalance could be a strong indication of the market momentum. Recently, Cont et al [19] examined the roles of order flow imbalance, trade imbalance, and the depth of LOB in affecting the price and found that order flow imbalance is a more general metric than the other two in limit order executions. Volume synchronized probability of informed trading (VPIN) is one of the well-known indicators developed by Easley et al [22] for modeling order flow imbalance.…”
Section: Related Statistical Issuesmentioning
confidence: 99%